The Kappa Opioid Receptor: A Promising Therapeutic Target for Multiple Pathologies - Dalefield, Martin L.; Scouller, Brittany; Bibi, Rabia; Kivell, Bronwyn M. (Frontiers in Pharmacology, 2022)
Kappa-opioid receptors (KOR) are widely expressed throughout the central nervous system, where they modulate a range of physiological processes depending on their location, including stress, mood, reward, pain, inflammation, and remyelination. However, clinical use of KOR agonists is limited by adverse effects such as dysphoria, aversion, and sedation. Within the drug-development field KOR agonists have been extensively investigated for the treatment of many centrally mediated nociceptive disorders including pruritis and pain. KOR agonists are potential alternatives to mu-opioid receptor (MOR) agonists for the treatment of pain due to their anti-nociceptive effects, lack of abuse potential, and reduced respiratory depressive effects, however, dysphoric side-effects have limited their widespread clinical use. Other diseases for which KOR agonists hold promising therapeutic potential include pruritis, multiple sclerosis, Alzheimer’s disease, inflammatory diseases, gastrointestinal diseases, cancer, and ischemia. This review highlights recent drug-development efforts targeting KOR, including the development of G-protein–biased ligands, mixed opioid agonists, and peripherally restricted ligands to reduce side-effects. We also highlight the current KOR agonists that are in preclinical development or undergoing clinical trials.